2021
DOI: 10.5772/intechopen.93721
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations in Epstein Barr Virus Infection

Abstract: The Epstein-Barr Virus (EBV), a member of the Herpesvirus family, occurs commonly and infects more than 90% of people worldwide. Most of systemic EBV infections throughout childhood and adulthood are typically asymptomatic or paucisymptomatic. Even though ocular involvements in EBV infections are infrequently reported, an increasing number of ocular manifestations have been previously reported. Ocular manifestation caused by EBV infection involved all segments of the eye, including oculoglandular syndrome, dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Furthermore, presuming the prevalence of EBV in the majority of the population, it appears that the switch from latent to lytic could have had an important play in the individuals with PFR compared with the control group. On the other hand, several studies also indicated ophthalmic manifestation due to EBV infection in oculoglandular syndrome, dry eye syndrome, dacryoadenitis, conjunctivitis, episcleritis, keratitis, uveitis, choroiditis, retinitis, retinal vasculitis, and papillitis (57). At this juncture, it is worthwhile mentioning that the development of retinitis could have multiple etiological agents (bacteria, fungi, and viruses).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, presuming the prevalence of EBV in the majority of the population, it appears that the switch from latent to lytic could have had an important play in the individuals with PFR compared with the control group. On the other hand, several studies also indicated ophthalmic manifestation due to EBV infection in oculoglandular syndrome, dry eye syndrome, dacryoadenitis, conjunctivitis, episcleritis, keratitis, uveitis, choroiditis, retinitis, retinal vasculitis, and papillitis (57). At this juncture, it is worthwhile mentioning that the development of retinitis could have multiple etiological agents (bacteria, fungi, and viruses).…”
Section: Discussionmentioning
confidence: 96%
“…These antibodies are found in 90% of adults with primary EBV infection (Womack & Jimenez 2015). IgM usually reaches its peak levels between the second and third week of an acute infection and may remain positive up to one year (Womack & Jimenez 2015;Andi Arus Victor 2020). The test has a 25% falsenegative rate in the first week of disease.…”
Section: Diagnosismentioning
confidence: 99%